Printed monopole antenna size miniaturization using fractal geometry and partial cutting method for L band application / Mohd Hassani Abbas - Abbas, Mohd Hassani (2016)
This paper present a study of Printed monopole Antenna design size miniaturization for L band application. Conventional antenna has been designed for performance and dimension size reference. Two steps of antenna design has been developed which is fractal geometry shape antenna and fractal geometry shape with partial cutting antenna to form the proposed antenna. Two miniaturization technique is applied to the proposed antenna. Each Fractal geometry and partial cutting techniques has been approached for each developed antenna respectively. In the study process, Conventional, Koch Fractal, Koch Fractal *Peano and Koch Fractal Peano with Partial Cutting antenna has been simulated. But only Conventional and Koch Fractal Peano with Partial Cutting antenna has been fabricated. Impedance matching and bandwidth performance of Conventional, Koch Fractal, Koch Fractal Peano and Koch Fractal Peano with Partial Cutting antenna has been compared through simulation and fabrication measurement. The proposed antenna and conventional printed monopole antenna dimension size has been compared. The proposed printed monopole antenna give the overall size is 16.00 x 43.06 x 1.67 mm is 39.88% smaller than conventional antenna